Medical statistics : a guide to SPSS, data analysis, and critical appraisal - Barton, Belinda; Peat, Jennifer K. (Wiley Blackwell : BMJ Books, 2014)
Medical Statistics provides the necessary statistical tools to enable researchers to undertake and understand evidence-based clinical research. It is a practical guide to conducting statistical research and interpreting statistics in the context of how the participants were recruited, how the study was designed, what types of variables were used, what effect size was found, and what the P values mean. It guides researchers through the process of selecting the correct statistics and show how to best report results for presentation and publication. Clear and concise explanations, combined wit.